Small Fiber Neuropathy - Zhou, Lan (Seminars in Neurology, 2019)
Small fiber neuropathy (SFN) is common, and can be associated with many medical conditions. The majority of the patients with SFN suffer from painful paresthesia which can negatively impact their quality of life. Skin biopsy with intraepidermal nerve fiber density evaluation is the gold standard diagnostic test. Autonomic function testing is useful when autonomic symptoms are present. Screening for associated conditions should be done in every patient, even when a known underlying associated condition is present, before the neuropathy evaluation. Etiology-specific treatment, lifestyle modification, and pain control are the key elements of SFN management. This article will review the clinical presentation, skin biopsy procedure, utility of diagnostic tests, associated conditions, management, and prognosis of SFN.
Keywords: small fiber neuropathy; skin biopsy; management